2018
DOI: 10.21746/aps.2018.7.4.22
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemical Mutagens on Chromosomal behavior of Allium cepa L

Abstract: Effect of chemical mutagens was studied in mitotic cells of Allium cepa L. For this purpose root tips were treated with saturated solution of peradichloro benzene, 0.2% EMS and 0.2 % freshly prepared colchicines for 4hours to 9hours.The studies revealed a wide range of chromosomal abnormalities such as stickiness, laggards, chromosomal bridge, unequal separation, nuclear budding, multinuclear cells etc.The parentage of chromosomal abnormalities in different mitotic stages were calculated on mitotic index, freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The experiment is also suggested to evaluate the genotoxic effects of novel nanomaterials and considered as a substitute to animal tests (Klančnik et al, 2011 ). Although severalphysico-chemical mutagens, metal-complexes, and Cu, CdS-NPs have been reported to induce chromosomal (Kumbhakar et al, 2016 ; Sharma et al, 2018 ), the cytotoxic effects of Ag-NPs are poorly reported. Root meristem of A. cepa was used to detect the cytotoxic effect of BP-AgNP S at three different concentrations (10, 20, and 30 μg/mL).…”
Section: Resultsmentioning
confidence: 99%
“…The experiment is also suggested to evaluate the genotoxic effects of novel nanomaterials and considered as a substitute to animal tests (Klančnik et al, 2011 ). Although severalphysico-chemical mutagens, metal-complexes, and Cu, CdS-NPs have been reported to induce chromosomal (Kumbhakar et al, 2016 ; Sharma et al, 2018 ), the cytotoxic effects of Ag-NPs are poorly reported. Root meristem of A. cepa was used to detect the cytotoxic effect of BP-AgNP S at three different concentrations (10, 20, and 30 μg/mL).…”
Section: Resultsmentioning
confidence: 99%
“…The A. cepa assay has been extensively used to research the genotoxicity of several mutagens, finding that these substances can induce chromosomal abnormalities in root meristems of A. cepa. It is an effective test for chemical screening and in-situ monitoring for genotoxicity of environmental pollutants (Jyotirmoy Sharma et al, 2018). In addition, the most effective method to change an organism's genetic makeup and produce the desired traits is mutation breeding.…”
Section: Introductionmentioning
confidence: 99%
“…So, expand the genetic variability of shallots is required. Increasing the genetic diversity of the shallot can be done through the induction of physical and chemical mutagens, as applied by [2,3,4,5]. Ethyl methanesulfonate (EMS) is a generally used chemical mutagen in plant breeding that can cause point mutations with higher frequency and produce genetic variation from which desired mutant may be selected.…”
Section: Introductionmentioning
confidence: 99%